2017
DOI: 10.1039/c6cp07269k
|View full text |Cite
|
Sign up to set email alerts
|

Designing hierarchical hollow nanostructures of Cu2MoS4 for improved hydrogen evolution reaction

Abstract: Layered CuMoS, consisting of earth-abundant elements, is regarded as a potential catalyst for the hydrogen evolution reaction (HER). Herein, we demonstrate a CuO-based template strategy to synthesise hierarchical hollow nanostructures of CuMoS. The characterizations reveal that the electrochemically active surface of the hollow CuMoS is largely enhanced, in contrast to the nanosheet or nanoparticle structures. As the direct outcome, the designed hierarchical hollow structures display excellent HER activities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…In this context, a well‐defined crystal structure of copper‐molybdenum‐sulfide (Cu 2 MoS 4 ), in which van der Waals interactions connect a tetragonal lattice and layers, has impressively shown active and robust catalysis over a wide range of pH values . Although diverse structures and morphologies of Cu 2 MoS 4 have been fabricated so far, enlarging electroactive surface area and high uniformity of Cu 2 MoS 4 still face challenges due to deficiency of active sites on the basal plane and unavailable well‐defined nanostructures …”
Section: Introductionmentioning
confidence: 99%
“…In this context, a well‐defined crystal structure of copper‐molybdenum‐sulfide (Cu 2 MoS 4 ), in which van der Waals interactions connect a tetragonal lattice and layers, has impressively shown active and robust catalysis over a wide range of pH values . Although diverse structures and morphologies of Cu 2 MoS 4 have been fabricated so far, enlarging electroactive surface area and high uniformity of Cu 2 MoS 4 still face challenges due to deficiency of active sites on the basal plane and unavailable well‐defined nanostructures …”
Section: Introductionmentioning
confidence: 99%
“…In this review, we summarized the recent advances in the controllable synthesis and photocatalytic applications of layered Cu 2 MX 4 nanomaterials. Figure shows the synthesis routes, the correlation between various material aspects and photocatalytic performance of Cu 2 MX 4 , indicating a high potential for efficient photodegradation of organic pollutant, water splitting and other applications . As discussed, modulations of synthesis routes can allow Cu 2 MX 4 nanomaterials to exhibit various morphologies with different characteristics, thereby enabling efficient and durable photocatalysis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 89%
“…[1][2][3][4][5][6][7] Copper molybdenum sulfide (Cu 2 MoS 4 ) was recently adapted to TTMCs, yielding two structural phases: allotropes in the P42m space group or in the I42m space group. [13][14][15] Cu 2 MoS 4 may be synthesized by refluxing a solution containing (NH 4 ) 2 MoS 4 with [Cu(CH 3 CN)](BF 4 ) in a DMF-acetonitrile solvent. [9][10][11][12] Cu 2 MoS 4 , in particular, is considered to be an efficient electrocatalyst for the hydrogen evolution reaction (HER).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Cu 2 MoS 4 may be synthesized by refluxing a solution containing (NH 4 ) 2 MoS 4 with [Cu(CH 3 CN)](BF 4 ) in a DMF-acetonitrile solvent. 8,15,19,20 Hierarchical hollow nanostructures composed of Cu 2 MoS 4 were obtained from Cu 2 O nanospheres 40-60 nm in size. 17 Cu 2 MoS 4 nanoparticles were prepared from CuCl, (NH 4 ) 6 Mo 7 S 24 , and Na 2 S by carrying out solid phase processes at 200 C. 18 Recently, the pioneering work of Song et al reported the synthesis and morphological evolution of Cu 2 MoS 4 nanostructures using Cu 2 O templates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation